Réseaux et gestion intégrée des zones côtières : un regard de géographes - Valérie Morel; Aude Körfer; Philippe Deboudt (VertigO)
Studying social networks related to Integrated Coastal Zone Management (ICZM) in Europe is a new way to approach ICZM from a different angle. Theoretically, this study permits to cross sociologic and geographic analyses. The aim of this study is to analyse how the actors, in particular actors from the scientific community, organize themselves and on which political scales - European, national, regional, local – they act. Another objective is to examine how the networking process itself contributes to ICZM. In order to understand the growing complexity of the networks, we characterise the networks with respect to their nature, their dynamics, their significance and their role for the development of ICZM. Networks related to ICZM take active part to the territorial reorganizations taking place on the European coastal areas.